(untitled) (Crimson Journal of Science and Technology, 2025)
Introduction: Hypertension and dyslipidemia are major modifiable risk factors for cardiovascular disease (CVD), the leading cause of global mortality. Fermented dairy products such as buttermilk contain bioactive peptides, probiotics, and milk fat globule membrane (MFGM) components that may beneficially influence vascular function and lipid metabolism. This study aimed to evaluate the impact of regular buttermilk consumption on blood pressure indices and lipid profiles in a Nepalese population, comparing habitual consumers with non-consumers. Methods: A cross-sectional study was conducted among 680 participants (n = 340 per group) in Gulmi District, Nepal. Blood pressure parameters (systolic, diastolic, and mean arterial pressure) and lipid markers (total cholesterol, triglycerides, LDL-C and HDL-C) were measured and compared between groups. Statistical significance was assessed using appropriate tests, with p < .05 considered significant. Results: Buttermilk consumption was associated with significant reductions in systolic blood pressure (p = .003) and mean arterial pressure (p = .012), though diastolic pressure changes were not statistically significant (p = .065). Lipid parameters showed robust improvements: total cholesterol and triglycerides were significantly reduced, while HDL cholesterol increased substantially. LDL-C reductions were significant in participants with elevated baseline levels but did not reach significance in the overall population Conclusions: Regular buttermilk intake appears to exert cardio protective effects through improvements in lipid profile and modest reductions in blood pressure. While lipid benefits are clinically relevant, blood pressure effects are limited, suggesting that buttermilk may serve as a supportive dietary measure rather than a primary intervention. Further long-term studies are warranted to confirm these findings and elucidate underlying mechanisms.